Van Rensselaer Potter, Climate Change, and Justice - Dwyer, James (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
When Van Rensselaer Potter coined the English word “bioethics”, he envisioned a field that would bring together biological understanding and ethical values to address global environmental problems. Following Potter’s broad vision of bioethics, I explore ethical ideas that we need to address climate change. However, I develop and emphasize ideas about justice and responsibility in ways that Potter did not. At key points, I contrast the ideas that I develop with those in Potter’s work, but I try to avoid scholarly debates and stay focused on the practical task: developing ideas to help us address climate change. To begin, I describe the problem of climate change. Then I show how it raises deep and serious issues of justice. Since the issues of justice are relatively clear and compelling, I proceed to focus attention on issues of responsibility – on why and how to respond to the structural injustices of climate change. I also note how my emphasis on justice and responsibility raises two new issues. To conclude, I mention the role of ecological citizens in bringing about social change.